If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -2y)(4x + y) = 0 Multiply (x + -2y) * (4x + y) (x(4x + y) + -2y * (4x + y)) = 0 ((4x * x + y * x) + -2y * (4x + y)) = 0 Reorder the terms: ((xy + 4x2) + -2y * (4x + y)) = 0 ((xy + 4x2) + -2y * (4x + y)) = 0 (xy + 4x2 + (4x * -2y + y * -2y)) = 0 (xy + 4x2 + (-8xy + -2y2)) = 0 Reorder the terms: (xy + -8xy + 4x2 + -2y2) = 0 Combine like terms: xy + -8xy = -7xy (-7xy + 4x2 + -2y2) = 0 Solving -7xy + 4x2 + -2y2 = 0 Solving for variable 'x'. Factor a trinomial. (x + -2y)(4x + y) = 0Subproblem 1
Set the factor '(x + -2y)' equal to zero and attempt to solve: Simplifying x + -2y = 0 Solving x + -2y = 0 Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. x + -2y + 2y = 0 + 2y Combine like terms: -2y + 2y = 0 x + 0 = 0 + 2y x = 0 + 2y Remove the zero: x = 2y Simplifying x = 2ySubproblem 2
Set the factor '(4x + y)' equal to zero and attempt to solve: Simplifying 4x + y = 0 Solving 4x + y = 0 Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 4x + y + -1y = 0 + -1y Combine like terms: y + -1y = 0 4x + 0 = 0 + -1y 4x = 0 + -1y Remove the zero: 4x = -1y Divide each side by '4'. x = -0.25y Simplifying x = -0.25ySolution
x = {2y, -0.25y}
| 4y+10=2y-16 | | (x-2y)(4x-y)= | | 18*what=504 | | 3x-5-5=-2x-35 | | 4q-2q=14 | | 27-7x=27-x | | X^2-tx=2 | | 18y-15y=15 | | 4(x-2)+7=5x | | 24x^3/6x | | [7x-2]=12 | | 24^3/6x | | 10a-8a=6 | | -27=3-5x | | [2x+3]=0 | | 12f=15 | | 7(x-2)=2x+31 | | 3x1/3-2x2/5 | | (12X2)/6= | | (12X2)/6 | | 36=60-3x | | 3x-x+2x=20 | | P=(Q-80)/-4 | | -21=7(v-9) | | 50x=75x^2+55x^4y^5 | | Q=80-4P | | 2x+3x=16+7x | | -11x-8+3x+5-1+8x+4= | | Sin(x)=300/750 | | 150=-16x^2+80x+96 | | 11x-127=3x-7 | | 5x-1.1=-0.34x |